SPACE MONITORING OF PASTURES OF THE EASTERN REGIONS OF THE STAVROPOL TERRITORY - A. V. Skripchinskiy; S. A. Antonov (Наука. Инновации. Технологии)
Introduction: As a result of the shortage of arable land in the Stavropol region is the transformation of agricultural land. It is possible to identify the extent of plowing pastures on the basis of spatial and temporal analysis of agricultural land through geographic information systems using space information. Materials and methods of research: visual decoding of pastures was carried Out on the basis of data from Landsat series spacecraft in the period from January 1990 to December 2018. Clarification of the identified pasture areas was made using index images of the NDVI coefficient. Results and discussion: In Budyonnovsk district of the Stavropol territory pastures are located primarily along river valleys. In the Arzgir district of Stavropol Krai, pastures are mainly conined to the Kumo-Manych depression and stretch along the Chograi reservoir in the Northern part of the district. The total area of pastures in 2018 in Budennovsky district amounted to 2,230 hectares, which is about 86% of the area of pastures in 1990. In the Arzgir district, the area of pastures is 76660 hectares in 2018, which is 13.6% less than the area of pastures in 1990. A 28-year time period square in Budyonnovsk the district decreased by 6020 ha, and in Arzgirskogo district at 12110 ha. Arzgirskogo in the district for 28 years period considerable areas of land have undergone changes in the boundaries of the Kuma-Manych depression. Also signiicantly reducing the area of pastures near the village of Steppe. In the Budennovsky district, pastures located to the East of the Kuma river valley have undergone changes to a greater extent. According to the degree of manifestation of water erosion, the study areas are among the five districts of the Stavropol territory most prone to erosion processes. Conclusions: In Budennovsk and Arzgirskogo districts of the Stavropol territory revealed a reduction of pastures during the study period. The most rapidly transformed pastures in the period from 2010 to 2018. Physical and geographical features of the areas are reflected in the size of pasture areas. Transformable pastures are located in the valleys of rivers and gullies, which in the future may affect the development of erosion processes on agricultural land.